2017
DOI: 10.1074/jbc.m117.785709
|View full text |Cite
|
Sign up to set email alerts
|

The Ror1 receptor tyrosine kinase plays a critical role in regulating satellite cell proliferation during regeneration of injured muscle

Abstract: The Ror family receptor tyrosine kinases, Ror1 and Ror2, play important roles in regulating developmental morphogenesis and tissue- and organogenesis, but their roles in tissue regeneration in adult animals remain largely unknown. In this study, we examined the expression and function of Ror1 and Ror2 during skeletal muscle regeneration. Using an skeletal muscle injury model, we show that expression of Ror1 and Ror2 in skeletal muscles is induced transiently by the inflammatory cytokines, TNF-α and IL-1β, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Interestingly, the Wnt5 and ROR1 promoter contains an NF-kB-binding site well conserved in mammalian orthologs, and canonical NF-kB activation can directly regulate the transcription of Wnt5a or ROR1. 17,29 Wnt5a binds to several receptor pseudokinases such as ROR1, ROR2, RYK, and PTK7 as well as to Wnt receptor Frizzled-5 and the complexity of its signaling depends largely on receptor expression, downstream effectors, and possible crosstalk with the canonical Wnt-pathway. 16 Therefore, the functional correlation between ROR1 and NF-kB in MCL cells could originate from NF-kB-mediated activation of Wnt5a signaling, but additional studies are needed to fully investigate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Wnt5 and ROR1 promoter contains an NF-kB-binding site well conserved in mammalian orthologs, and canonical NF-kB activation can directly regulate the transcription of Wnt5a or ROR1. 17,29 Wnt5a binds to several receptor pseudokinases such as ROR1, ROR2, RYK, and PTK7 as well as to Wnt receptor Frizzled-5 and the complexity of its signaling depends largely on receptor expression, downstream effectors, and possible crosstalk with the canonical Wnt-pathway. 16 Therefore, the functional correlation between ROR1 and NF-kB in MCL cells could originate from NF-kB-mediated activation of Wnt5a signaling, but additional studies are needed to fully investigate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that increased ectopic coexpression of ROR1 and Wnt5a resulted in increased NF-kB transcription activation, suggesting a direct link between ROR1 expression and NF-kB activation. 28,29 Thus, we overexpressed ROR1 together with NF-kB p65 luciferase reporter in Mino cells and observed a direct correlation between ROR1 levels and NF-kB p65 transcription activation (threefold activation of NF-kB p65 luciferase reporter; Figure 2E). Collectively, these results identified NF-kB p65 as new downstream effector of ROR1 signaling in MCL.…”
Section: Ror1 Silencing Inhibited Cell Growth and Disrupted Nf-kb Sigmentioning
confidence: 99%
“…In MCL (mantle cell lymphoma) models, Wnt5a‐ROR1 expression was found to be associated with canonical NF‐κB pathway activation and drug resistance . This is supported by the presence of NF‐κB binding sites in the promoters of both Wnt5a and ROR1, providing a feedback activation loop Wnt5a/ROR1/NF‐κB p65 regulating cell proliferation, survival, and drug resistance . Inhibition of the B‐cell receptor (BCR) pathway impaired ROR1 levels even in the absence of NF‐κB p65 downregulation, a process that is very important for targeted treatment strategies.…”
Section: Ror Signaling In Hematological Cellsmentioning
confidence: 99%
“…Our findings identified ROR1 as a new interacting partner for MuSK, Dok‐7, and LRP4. ROR1 interaction with multiple proteins expressed in myogenic cells can be used to ascertain its roles in muscle regeneration and muscular disorders as previously suggested , while providing clues about signaling pathways employed by ROR1 in these cells.…”
Section: Discussionmentioning
confidence: 98%